2020
DOI: 10.1002/jat.4096
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis reveals cytotoxicity induced by graphene oxide exposure in A549 cells

Abstract: Several studies in recent years have demonstrated the broad application prospects of graphene and its derivatives in many fields such as composite material industry, energy storage, antimicrobial materials, and biomedicine. Large‐scale production and wide application also bring greater potential exposure risks, and there has been an increasing concern about the potential health hazards of graphene nanomaterials. In the present study, we exploited nonlabeled proteomics and bioinformatics analysis to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Therefore, the inhibitory effects of GQDs on K + and Ca 2+ channel should be adequately evaluated by combing with other physiological responses. Our nding about the transcriptional regulation of spliceosome triggered by GQDs was also reported in A549 cell line and zebra sh treated with GO [58,59], implying that the pathway could be commonly aroused by GQDs and other graphene derivatives. Splicing factors such as splicing factors 3b (SF3B) have been reported as a core target for anticancer treatment [60], and in this study ve splicing factors (srsf2a, sf3b1, srf4, srsf5a, and zgc: 163098) from the spliceosome pathway were all signi cantly downregulated by the four GQDs, indicating the potential of GQDs as spliceosome inhibitors or adjuvants for targeted cancer therapy.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, the inhibitory effects of GQDs on K + and Ca 2+ channel should be adequately evaluated by combing with other physiological responses. Our nding about the transcriptional regulation of spliceosome triggered by GQDs was also reported in A549 cell line and zebra sh treated with GO [58,59], implying that the pathway could be commonly aroused by GQDs and other graphene derivatives. Splicing factors such as splicing factors 3b (SF3B) have been reported as a core target for anticancer treatment [60], and in this study ve splicing factors (srsf2a, sf3b1, srf4, srsf5a, and zgc: 163098) from the spliceosome pathway were all signi cantly downregulated by the four GQDs, indicating the potential of GQDs as spliceosome inhibitors or adjuvants for targeted cancer therapy.…”
Section: Discussionsupporting
confidence: 67%
“…In agreement with our results, the concentration dependency has previously been reported for NIH 3T3 and A549, with much greater toxicity of GO for the normal cells, while discrepancies about time dependency are reported in the literature. 46,47 Another parameter that might affect the results is the test used. MTT and WST-8 assays were used in previous work to study the cytotoxicity of GO flakes and it was observed that GO interfered with the reagents, giving inaccurate results.…”
Section: Papermentioning
confidence: 99%
“…Exposure time of 48 h was chosen as transfections with commercially available kits such as lipofectamine typically require 48 h, and the concentrations were selected based on our previous work. We and others 62,63 have previously reported that the cytotoxicity of GO formulations can vary based on cell lines. For example, 3D spheroids generated from lung (A549) and leukemia (NB4) cancer cell lines showed noticeable toxicity only at 16 and 64 μg/mL but not at 1 and 4 μg/mL.…”
Section: ■ Results and Discussionmentioning
confidence: 82%